Prevalence of Treponema Pallidum Antibody among Volunteer Blood Donors in China. (8th August 2022) - Zheng, Xiaofan; Ding, Wei; Ling, Xia; Shi, Jie; Dong, Jie; Yu, Guangshu; Chen, Yan; Li, Rui; Xu, Lihong; Li, Xiaotao; Zhu, Hong; Zhu, Faming; et al.
Abstract : Background . Infection with syphilis is still a major public health problem. The precise data for syphilis seroprevalence in the populations will help to develop a strategy for prevention and treatment of it. However, the data for syphilis prevalence in continuous years among volunteer blood donors in China is rare. Methods . A retrospective study for Treponema pallidum (TP) antibody in blood donors was conducted from January 2010 to December 2019 at the Blood Center of Zhejiang Province, China. TP antibody was detected with two different reagents using enzyme-linked immunosorbent assay and the only sample which was reactive in the two reagents was defined as seropositive. Results . A total of 992, 646 volunteer blood donors were analyzed and the positive rate of TP antibody in the blood donors was 0.43%. From 2010 to 2019, the positive rates of TP antibody were 0.53%, 0.51%, 0.51%, 0.43%, 0.36%, 0.18%, 0.11%, 0.12%, 0.11%, and 0.10%, respectively. The positive rates of TP antibody were significantly different among blood donor age group (p < 0.001 ), with the highest positive rate in 45–54-years-old group (0.93%). The positive rates of TP antibody in male and female blood donors were 0.44% and 0.41%, respectively. The positive rate was 0.57% among the first-time blood donors, which was significantly higher than that of the repeat blood donors (0.17%). The positive rate of TP antibody in blood donors decreased gradually with the increase of educational level. Conclusion . The syphilis seroprevalence is low in the blood donors of the Hangzhou area, and the positive rate of blood donors is associated with age, educational level, and times of blood donation. Increasing the number of repeat blood donations is helpful to improve blood safety.